Direct Targeting of VMS through Amplitude Consistent Seismic Imaging - Yavuz, S; Kinkela, Jai; Greenwood, Andrew; Penney, M.; Araujo, V.; Neto, R.; Dzunic, Aleksandar; Urosevic, Milovan (EAGE, 2013)
Based on physical property measurements of core samples and the often observed difference in elastic properties from these there should be a significant difference in seismic amplitude between mineralisation and the surrounding host rocks. These results indicate that relative amplitude preservation processing may be of importance in the use of seismic data for the targeting of mineral resources, particularly in the case of massive ores. Such ‘true relative amplitude’ processing is not easy to achieve due to intrinsically low signal to noise ratio in hard rock environments, complex 3D geology, steeply dipping structures, high seismic velocities and often patchy and poor reflectivity. To help reduce the ambiguity in targeting and increase the likelihood of success we have worked on careful re-processing of 3D seismic data with the application of true amplitude preservation. We compare the anomalous amplitude zones that are related to massive sulphide bodies using a true amplitude seismic cube and a conventionally processed cube with the application of AGC (automatic gain control). A higher level comparison is conducted after seismic calibration with boreholes. The zonation and precision of targeting is discussed in this paper.